2019
DOI: 10.1128/mra.00239-19
|View full text |Cite
|
Sign up to set email alerts
|

Complete Whole-Genome Sequences of Two Raoultella terrigena Strains, NCTC 13097 and NCTC 13098, Isolated from Human Cases

Abstract: Raoultella terrigena is a bacterial species associated with soil and aquatic environments; however, sporadic cases of opportunistic disease in humans have been reported. Here, we report the first two complete genome sequences from clinical strains isolated from human sources that have been deposited in the National Collection of Type Cultures (NCTC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…The results also showed that the PCM8 strain had 393 subsystems with a coding sequence of 5513 (0,096%) and 117 RNA. This result is close to the results of the research of Fazal et al (2019) which states that the R. terrigena strain NCTC 13097 has a nucleotide base of 5.574.669 bp and a GC content of 57,3% with 5,386 coding sequences and 119 RNA genes. Even so, this study has not analyzed the genomic function of R. terrigena strain NCTC 13097 so it is not known whether this strain has the acdS gene.…”
Section: Ani Value Analysis Results and Wgs Annotations Of The Acds Gensupporting
confidence: 90%
“…The results also showed that the PCM8 strain had 393 subsystems with a coding sequence of 5513 (0,096%) and 117 RNA. This result is close to the results of the research of Fazal et al (2019) which states that the R. terrigena strain NCTC 13097 has a nucleotide base of 5.574.669 bp and a GC content of 57,3% with 5,386 coding sequences and 119 RNA genes. Even so, this study has not analyzed the genomic function of R. terrigena strain NCTC 13097 so it is not known whether this strain has the acdS gene.…”
Section: Ani Value Analysis Results and Wgs Annotations Of The Acds Gensupporting
confidence: 90%
“…Endophytes as a ubiquitous associate of the plant are considered to play a pivotal role in regulating the primary and secondary metabolism of their host plant, and in providing elicitors to improve plant health, ameliorating stress tolerance in plants and source of therapeutically important secondary metabolites ( Pandey et al, 2022 ). R. terrigena is considered to be an environmental bacterium, which is isolated mainly from soil and aquatic environments ( Fazal et al, 2019 ). It is also isolated from plant roots of Nicotiana tabacum and switchgrass Panicum virgatum , and considered to be an endophytic nitrogen-fixing bacterium ( Schicklberger et al, 2015 ; Gushgari-Doyle et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…One of the strains also contained an 86 kb plasmid. Bioinformatic analysis of the R. terrigena genome identified 5500 protein‐coding sequences in addition to 85 tRNA and 25 rRNA sequences 21 …”
Section: Discussionmentioning
confidence: 99%